Innovative Approaches and Traditional Methods: Constructing Qiroatul Kutub Learning in South Sumatran Islamic Boarding Schools - Anang Walian; Abdurrahmansyah Abdurrahmansyah; Kusnadi Kusnadi (STAI Hubbulwathan Duri, 2025)
Qiroatul kutub is a critical language skill in pesantren education. Despite its importance, preliminary research indicates that only 30% of students in South Sumatra's pesantren can proficiently read classical Arabic texts, known as the yellow book. This gap highlights the need to examine how various pesantren implement qiroatul kutub learning. This qualitative study employed a phenomenological design to explore learning constructions in traditional, semi-modern, and modern pesantren. Data were collected through structured interviews, participatory observation, and documentation. Analysis followed Miles and Huberman's interactive model: data reduction, data display, and conclusion drawing/verification. Findings reveal commonalities in the use of classical texts, focus on Arabic grammar (Nahwu and Shorf), Arabic proficiency development, and the overarching goal of producing Islamic scholars. Differences emerged in teaching methods, curricula, subject focus, and linguistic approaches. Traditional pesantren retain classical techniques such as sorogan, bandongan, muhafazhoh, tarjamah, and bahtsul masail. In contrast, semi-modern and modern pesantren integrate these with contemporary educational methods. The study concludes that each pesantren type adapts its qiroatul kutub system in line with its institutional identity and vision. Understanding these variations can inform strategies to enhance classical text literacy among pesantren students